2018
DOI: 10.1097/aln.0000000000002105
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Catheter Use and Infection in Regional Anesthesia

Abstract: Background Prolonged catheter use is controversial because of the risk of catheter-related infection, but the extent to which the risk increases over time remains unknown. We thus assessed the time-dependence of catheter-related infection risk up to 15 days. Methods Our analysis was based on the German Network for Regional Anesthesia, which includes 25 centers. We considered 44,555 patients who had surgery between 2007 and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 29 publications
2
26
0
5
Order By: Relevance
“…Single-shot wound infiltration may provide adequate analgesia, but effectiveness is limited by the pharmacokinetic properties of the selected drug, making prolonged analgesia less reliable. CWI allows continuous administration of local anesthetic with or without non-steroidal anti-inflammatory drugs throughout the postpartum period for up to 4 days 52. As with any indwelling catheter, risks for infection and catheter migration can occur.…”
Section: Continuous Wound Infiltrationmentioning
confidence: 99%
“…Single-shot wound infiltration may provide adequate analgesia, but effectiveness is limited by the pharmacokinetic properties of the selected drug, making prolonged analgesia less reliable. CWI allows continuous administration of local anesthetic with or without non-steroidal anti-inflammatory drugs throughout the postpartum period for up to 4 days 52. As with any indwelling catheter, risks for infection and catheter migration can occur.…”
Section: Continuous Wound Infiltrationmentioning
confidence: 99%
“…Bomberg et al reported the incidence of catheter‐associated infection as 1% after catheter use for 4 days, but a significant increase to 5% after 7 days. Furthermore, progression of the infection from mild to moderate was evident within 1.7 days if the catheter was not removed immediately 22 . In our study, most epidural catheters were removed on the fifth day and as soon as possible if signs of infection were observed.…”
Section: Discussionmentioning
confidence: 67%
“…The risk of using PCEA is extremely low. Infection, for example, is essentially a nonissue if the catheter is maintained in situ for 4 days or fewer (Bomberg et al, 2018). In our case, because our parturient was so pleased with her lack of pain, she elected to keep the PCEA in place until a few hours prior to discharge home.…”
Section: Discussionmentioning
confidence: 99%